Decomposition of consumer price index for Turkey - Baydan, Emel (My University, 2019)
Bu tez Türkiye’de bölgeler arasında fiyatlar seviyesinde yakınsama varlığını araştırmaktadır. Bölgesel yakınsama tartışmaları büyüyerek artmaktadır ve düzinelerce çalışma yapılmaktadır bu konu hakkında. Neoklasik büyüme teorisiyle kazandırılan yakınsama teoremi fiyat yakınsaması açısından incelenmektedir. Eğer yakınsama gerçekleşirse bu fiyat tutarlılığı (kararlılığı) var anlamına gelmektedir. Yakınsama kavramı politika yapıcılar ve iş dünyası açısından çok büyük öneme sahiptir. Globalleşme ve Liberalleşme ile birlikte daha da çekici hale gelmektedir. Tüketici fiyat endeksi kullanılarak yapılan yakınsama araştırmaları, alım gücü paritesi, tek fiyat kanunu, enflasyon ve bununla birlikte kişi başına düşen milli gelir verileri ile de büyüme hakkında bize ip uçları vermektedir. Bu çalışma fiyat yakınsamasını fiyat ve enflasyon oranı açısından incelemektedir.Türkiye İstatistik Kurumu tarafından oluşturulan, 12 ana mal ve hizmetler grubunun her birinden 5’er tane mal ve hizmet seçilerek 60 tane mal ve hizmet oluşturulup 81 ili içeren 26 bölgede ki fiyat yakınsaması incelenmiştir. Yarıparametrik metotlar aracılığıyla ki bu çalışmada (Shimotsu, 2004; Shimotsu & Phillips, 2004) tarafından geliştirilen parçalı bütünleşme analizi, LW, 2ELW and 2ELWd kullanılmıştır. Türkiye’de kısa dönem hafızayla birlikte bölgeler arasında yakınsama olsuğuna dair kanıtlar bulunmuştur.

This thesis is examining the price level convergence among regions whithin Turkey. The debate on regional convergence has bred, and continues to do so, dozens of empirical studies investigate this. The convergence theory, which emerged with the Neoclassical growth model, is also examined in terms of price convergence. If convergence is valid, this implies that price stability exists. The convergence is crutial for the policy makers and businesses. With the increasing globalization and liberalizations, it even become more attractive.The investigation of convergence using with consumer price index results give us clues about inflation, purcahsing power parity and law of one price and beside growth by using income per capita data.In order to analyze price convergence, the price of sixty ‘goods and services have been formed by selecting five goods and services from each twelve main group for the eighty-one provinces which form of the twenty-six regions of Turkey. The data is taken from the Turkish Statistical Institude (Turkstat).I employ semiparametric methods, which are the Local whittle estimation (LW), two step Exact local whittle estimation (2ELW) and two step Exact l ocal whittle estimation with de-trending (2ELWd), developed by (Shimotsu, 2004; Shimotsu & Phillips, 2004).The thesis focuses on the regional convergence in terms of “ good and service” price. I obtain empirical results that demonstrate that LW, 2ELW and 2ELWd estimation methods produce short memory on regional convergence in Turkey.
Keywords: Bölgesel ekonomik aktivite Price level; Finance; Fiyat seviyesi; Maliye; Regional economic activity; Semiparametric and Nonparametric methods; Yarıparametrik ve Parametrik olmayan metotlar